Pengaruh Kompetensi, Kompensasi Dan Motivasi Terhadap Kinerja Guru PNS Bersertifikasi pada SMP Negeri 7 palembang - Yuniarti, Yuniarti (Utan Kayu Publishing, 2021)
This study aims to determine the effect of Competence, Compensation and Motivation on the Performance of Certified Teachers in SMP Negeri 7 Palembang. In this study, the sample taken was all teachers with the status of Certified Civil Servants, totalling 40 people as samples of trial data and research data. In this study, the sampling technique is done by using the saturated sampling technique that is all populations are sampled regression equations. From the results of this study, there is a positive and significant influence simultaneously Competency, Compensation and Motivation on the Performance of Certified Civil Servants Teachers in Palembang 7 Public Middle School, which is proven by the sig F value of 0,000 less than α (0.05). There is a positive and significant effect of Competence on the Performance of Certified Teachers in Palembang 7 Public Middle School with a sig t value of 0,000 less than α (0.05). There is a positive and significant effect of Compensation on the Performance of Certified Teachers in SMP Negeri 7 Palembang with a sig t value of 0.007 less than α (0.05). There is a positive and significant influence of Motivation on the Performance of certified Teachers in Palembang 7 Public Middle School with a sig t value of 0.049 less than α (0.05). Correlation (R) influence variables Competency (X1), Compensation (X2) and Motivation (X3) together to the Performance of Certified Teachers (Y) is 0.625 meaning the relationship of Competence, Compensation and Motivation together with the Performance of Certified Teachers Palembang 7 Public Middle School showed a strong and positive correlation. The coefficient of determination (R-square) is 0.391 which gives an understanding that 39.1% of the Performance of Certified Civil Servant Teachers (Y) can be explained or influenced by Competency (X1), Compensation (X2) and Motivation (X3) together while the remaining 60, 9% is influenced by other factors not examined